Effect of load parameter on tribological behavior of UHMWPE/Pongamia oil-cake incorporated basalt epoxy composites. (2020) - Mohan, N.; Tavadi, Ashok Kumar R.; Chetan, K.; AkshayPrasad, M.
Abstract: The wear nature of basalt epoxy specimens incorporated with both POC and UHMWPE was studied by using wear test tribometer. The wear rate was calculated with respect to applied load. The test specimens were formulated using VARTM technique. The % of filler material in the specimen was varied from 0 wt% to 6 wt% (POC and UHMWPE). The outstanding wear behavior was recovered with basalt composites with the fillers. The fracture surface of the specimens was examined by using high resolution scanning electron microscope to analyze the wear data. It was observed that addition of fillers is very important when the worn out of the specimen at initial stages. The process of tribo-film, fibre breakages accounts for wear at much later stages.